The social experiences and academic challenges faced by students with albinism in the University of Limpopo - Baloyi, D. I. (University of Limpopo, 2019)
Students with albinism experience social and academic challenges in society. These challenges are mainly influenced by their disability. Studies indicate that because they look different from most people they are treated differently and socially excluded and marginalised. Albino individual’ are also murdered in South Africa which is motivated by myths, beliefs and misconceptions in traditional African societies. The Social Model of Disability (SMD) underpinned the study as it is used to explore social experiences in different life contexts. The study used a qualitative approach with an exploratory research design. Purposive sampling was used to select the 18 participants. Thematic Content Analysis (TCA) was used to analyse data collected from the three focus groups. The findings of the study revealed that the social experiences of students with albinism are be difficult. They experience discrimination and stigmatisation from their peers and are often called derogatory names. It was also found that students with albinism have academic challenges because of their impaired vision, lecturers’ negative attitudes and insensitivity towards them. It was also found that the lack adequate assistive devices. Social experiences and academic challenges lead to a self-reported negative impact for instance, depression for these students. Ultimately, more awareness initiatives about the condition are required at the institution in order to improve the experiences of students with albinism.
Thesis (M. A. (Clinical Psychology)) --University of Limpopo, 2019
Keywords: Albinism; Depression; Academic challenges; Disability; Myths; Disability; Myths; Albinos and albinism